Victimization and Resilience Among Sexual and Gender Minority Homeless Youth Engaging in Survival Sex - Alessi, Edward J. (Journal of interpersonal violence, 2021)
This study examined how a diverse group of sexual and gender minority (SGM) homeless youth described and understood their victimization experiences occurring before they were homeless and those occurring after they were homeless and engaging in survival sex. In addition, the study explored how these youths manifested resilience when living on the street. The sample consisted of 283 racially/ethnically diverse youth between the ages of 15 and 26 years (M = 19.6, SD = 1.28) living in a large U.S. city. Participants identified their gender as male (47%), female (36%), transgender (15%), or queer and other (3%) and their sexual orientation as bisexual (37%), gay (23%), lesbian (15%), heterosexual (13%), or queer and other (13%). Thirty-seven percent identified as Black, 30% as multiracial, 22% as Latino/a, 5% as White, and 5% as another race. Content and thematic analyses were used to conduct a secondary analysis of qualitative data. Four themes were identified: unsafe and unsupported at home; barriers to housing and employment stability; ongoing victimization and lack of protection; and unexpected opportunities for resilience. Findings demonstrated that participants experienced victimization related not only to their SGM identities but also to chaotic home environments. Once homeless and engaging in survival sex, youth experienced barriers to securing employment and housing as well as victimization by police and clients. These experiences frequently involved prejudice related to their intersecting identities. Despite encountering numerous challenges, participants described surviving on the streets by living openly and forming relationships with other youth. Implications for practice and policy are discussed.